Accelerating recovery from exercise-induced muscle injuries in triathletes: Considerations for Olympic distance races - Hotfiel, T.; Mayer, I.; Huettel, M.; Hoppe, M. W.; Engelhardt, M.; Lutter, C.; Pöttgen, K.; Heiss, R.; Kastner, T.; Grim, C. (Sports, 2019)
The triathlon is one of the fastest developing sports in the world due to expanding participation and media attention. The fundamental change in Olympic triathlon races from a single to a multistart event is highly demanding in terms of recovery from and prevention of exercise-induced muscle injures. In elite and competitive sports, ultrastructural muscle injuries, including delayed onset muscle soreness (DOMS), are responsible for impaired muscle performance capacities. Prevention and treatment of these conditions have become key in regaining muscular performance levels and to guarantee performance and economy of motion in swimming, cycling and running. The aim of this review is to provide an overview of the current findings on the pathophysiology, as well as treatment and prevention of, these conditions in compliance with clinical implications for elite triathletes. In the context of DOMS, the majority of recovery interventions have focused on di erent protocols of compression, cold or heat therapy, active regeneration, nutritional interventions, or sleep. The authors agree that there is a compelling need for further studies, including high-quality randomized trials, to completely evaluate the e ectiveness of existing therapeutic approaches, particularly in triathletes. The given recommendations must be updated and adjusted, as further evidence emerges.